Imobilização de metais presentes no lodo de esgoto a partir da vermicompostagem e produção de alface (Lactuca sativa) - Machado, Lilian Patrícia de Ramos (2022)
Due to the complexity of some heavy metals, their presence in sewage sludge, make the feasibility of using this material somewhat restrictive, as the difficulties in eliminating these elements cause concern when it comes to its purpose and/or use in an adequate and safe in agriculture. The study in question aimed to treat the sludge from the sewage treatment plant for metals As, Ba, Cd, Cr and Ni, through the vermicomposting technique, with concentrations of 30, 20, 15, 12.5, 10, 7.5 and 5% of sewage sludge, to verify the possible reduction or elimination of these elements by the action of the earthworms and to evaluate whether or not there was transfer of metals to the lettuce parts, after being planted in material with proportions of 15, 12.5, 10, 7.5 and 5% sewage sludge. The materials were prepared with a commercial substrate mix. At the end of the experiment, it was concluded that the earthworms had the ability to reduce the Ba, Cd, Cr and Ni elements of the prepared material, however, for As, the vermicomposting technique was unsuccessful. As for the lettuce seedlings planted with doses of sludge, accumulation in the roots was identified only for the metals As and Cr, and Cr was also found in the leaves. Showing that there is low mobility of metals of interest in plants.